1985
DOI: 10.1111/j.1365-2125.1985.tb02713.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological experiments in healthy volunteers with bopindolol, a long‐acting beta‐adrenoceptor blocking drug with partial agonist activity.

Abstract: 1 Bopindolol is a potent and specific ,3-adrenoceptor antagonist with partial agonist activity. In animal experiments it blocks both ,Bl-and P2-adrenoceptors and possesses a long duration of action. In the present study in healthy volunteers bopindolol was about ten times more potent than pindolol in reducing isoprenaline-induced and exerciseinduced tachycardia.2 In experiments on exercise-induced tachycardia an oral dose of 2 mg produced a near maximum reduction of exercise heart rate, occurring within 2 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
2
19
0
1
Order By: Relevance
“…There is increasing evidence that bopindolol possesses long-acting ß-blocking action with high affinity and partial agonist activity to the ß-ARs in both healthy volunteers and animal models [9,11,13,14], suggesting that less frequent administration may be necessary than with most other ß-blockers [6,7,11]. It is well known that one active metabolite (18-502) also has strong ß-blocking action, suggesting that this metabolite also contributes to the long-lasting effects of bopindolol [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that bopindolol possesses long-acting ß-blocking action with high affinity and partial agonist activity to the ß-ARs in both healthy volunteers and animal models [9,11,13,14], suggesting that less frequent administration may be necessary than with most other ß-blockers [6,7,11]. It is well known that one active metabolite (18-502) also has strong ß-blocking action, suggesting that this metabolite also contributes to the long-lasting effects of bopindolol [2].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain its long-lasting antihypertensive effects. Although these long-acting pharmacological effects of bopindolol have also been demonstrated in animal models [6], healthy volunteers [7,8], and patients with hypertension [9], the precise mechanisms are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that it is a non-selective antagonist with a long duration of action of at least 24 h, suggesting that less frequent administration may be necessary than with most other P-adrenoceptor blockers (Aellig, 1982). We report a detailed study of its haemodynamic effects during exercise and passive tilting in six healthy young men.…”
Section: Introductionmentioning
confidence: 99%
“…The long duration of action of bopindolol found in animal experiments was confirmed in man. Forty-eight hours after an oral dose of 4 mg, about 38% of the maximum effect was still present (Aellig, 1985).…”
Section: Introductionmentioning
confidence: 99%